Diagnóstico dos resíduos de construção e demolição para elaboração e implantação da gestão integrada dos RCD no município de Guanambi – BA - Neves, Gustavo Silveira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Taking as starting the environmental, social and economic impact of construction and demolition waste in Brazilian cities were created legal mechanisms for management and administration, seeking to minimize the impacts to the maximum, since the irregular deposition can be characterized as environmental crime. CONAMA Resolution No. 307 of 2002 establishing the mandatory implementation of an Integrated Management System Construction Waste and Demolition, guiding the classification and designation of the waste generating agents, collection agents and transporters, and the areas of culling and disposal of waste. The technical partnership between the Ministry of Cities, the Environment Ministry and the Caixa Econômica Federal, coordinated by Pinto & Gonzales (2005) Management in the work and management of construction waste, proposed a guidance manual to guide the implementation of a System Integrated Management of Construction Waste in Municipalities. The municipality of Guanambi in the state of Bahia, in full economic rise, lacks a waste management of construction and demolition, since there has areas for the disposal of waste being proposed in this paper the diagnosis of waste generation in the municipality as part of the methodology proposed by the work of Pinto & Gonzales (2005).

Tomando como partida o impacto ambiental, social e econômico causado pelos resíduos de construção e demolição nas cidades brasileiras, foram criados mecanismos legais para gestão e manejo, procurando minimizar ao máximo os impactos, visto que as deposições irregulares podem se caracterizar como crime ambiental. A Resolução CONAMA Nº 307 de 2002, institui a obrigatoriedade da implantação de um Sistema de Gestão Integrada de Resíduos de Construção e Demolição, orientando na classificação e denominação dos resíduos, agentes geradores, agentes coletores e transportadores, e as áreas de descarte e disposição dos resíduos. A parceria técnica entre o Ministério das Cidades, o Ministério do Meio Ambiente e a Caixa Econômica Federal, coordenada por Pinto & Gonzáles (2005) na obra Manejo e gestão de resíduos da construção civil, propuseram um manual de orientação para nortear a implantação de um Sistema de Gestão Integrada de Resíduos de Construção Civil nos Municípios. O município de Guanambi, no estado da Bahia, em plena ascensão econômica, carece de uma gestão dos resíduos de construção e demolição, visto que não apresenta áreas próprias para o destino dos resíduos, sendo proposto neste trabalho o diagnóstico da geração de resíduos do município como parte integrante da metodologia proposta pela obra de Pinto & Gonzáles (2005).
Keywords: Resíduos sólidos; Construção civil; Agregados (Materiais de construção); Industria de construção civil - Aspectos ambientais; Reaproveitamento (Sobras, refugos, etc.); Demolição; Recycling(Waste, etc.)